Las letras del cancionero nacional como estrategia metodológica para la enseñanza de la poesía, en la asignatura de lengua y literatura, en los estudiantes del segundo de bachillerato del Colegio de Bachillerato U.N.E. de la ciudad de Machala, periodo lectivo 2014-2015. - Gallegos Gaona, Pedro Hernán (2014)
Every art form has a language , a vehicle through which man conveys ideas and feelings. Our music identifies us with their cultural expressions and linguistic content , where different music having ethnic and cultural diversity of Ecuador .